Analisis Kandungan Zat Besi Ubi Jalar Ungu dan Keripik Ubi Jalar Ungu - Elisa Oktaviana; Nurmayani, Winda (Universitas Qamarul Huda Badaruddin, 2025)
As a food ingredient, sweet potato tubers have a fairly high nutritional content. Iron is an essential component of hemoglobin, a protein in red blood cells that is responsible for binding and transporting oxygen from the lungs throughout the body, and is necessary for cellular metabolism, energy production, and overall tissue function. The purpose of this study was to analyze the iron content of purple sweet potatoes and purple sweet potato chips. This research is a quantitative field research, with the design in this research being a completely randomized design (CRD). Research on the analysis of iron content in purple sweet potatoes and purple sweet potato chips was conducted at the Main Laboratory Center of the University of Mataram. This research uses a method that complies with SNI 01-2891-1992 and is supported by adequate laboratory equipment with the assistance of expert researchers. Based on the laboratory tests that have been carried out, the analysis results obtained are that in 100 grams of purple sweet potatoes there are 11.14 mg of iron, while purple sweet potatoes that have been processed by heating with cooking oil into chips have a reduced iron content to 10.01 mg in 100 grams. The iron content in purple sweet potatoes is higher than the iron content in purple sweet potatoes that have been heated with cooking oil, namely purple sweet potatoes that have been processed into chips from 11.14 to 10.01 mg in 100 grams. So if consumed, the body will get more sources of iron from purple sweet potatoes that have not been processed by heating.